THE INFLUENCE OF PROFITABILITY, LIQUIDITY, AND DEBT TO THE DIVIDEND PAYOUT RATIO IN MANUFACTURING COMPANY (LISTED IN INDONESIAN STOCK EXCHANGE FROM 2008-2010) - Putri Kartika Sari; Sigit Handoyo (Jurnal Siasat Bisnis, 2013)
AbstractThis research analyzes the influence of profitability, liquidity, and debt to dividend payout ratio in manufacturing companies in Indonesia. The samples consist of 102 companies listed in Indonesian Stock Exchange during the period of 2008-2010. This research tests three hypotheses related to the influence of profitability, liquidity, and debt toward the dividend payout ratio (DPR). Data obtained were analyzed by using multiple regression analysis. The results of this research indicate that: (1) profitability ratio (ROI) has positively significant influence to dividend payout ratio. (2) Liquidity ratio (QR) does not significantly influence to dividend payout ratio. (3) Debt ratio (DER) does not significantly influence to dividend payout ratio.Keywords: profitability, liquidity, debt, Dividend Payout Ratio (DPR), manufacturing company.AbstrakPenelitian ini bertujuan untuk menganalisis pengaruh profitabilitas, likuiditas, dan utang terhadap rasio pembayaran dividen dalam perusahaan-perusahaan manufaktur di Indonesia. Sampel terdiri dari 102 perusahaan yang terdaftar di Bursa saham Indonesia selama periode tahun 2008-2010. Penelitian ini menguji tiga hipotesa yang berkaitan dengan pengaruh profitabilitas, likuiditas, dan utang terhadap rasio pembayaran dividen (DPR). Data yang diperoleh dianalisis dengan menggunakan analisis regresi. Hasil dari penelitian ini menunjukkan bahwa: (1) profitabilitas rasio (ROI) memiliki pengaruh positif dan signifikan terhadap rasio pembayaran dividen. (2) rasio likuiditas (QR) tidak berpengaruh terhadap rasio pembayaran dividen. (3) Rasio hutang (DER) tidak berpengaruh atas rasio pembayaran dividen.Kata kunci: profitabilitas, likuiditas, utang, rasio pembayaran dividen (DPR), manufaktur perusahaan.